(untitled) (Impact: Journal of Transformation, 2024)
This paper examines the sociolinguistic situation of the Runga people group in Chad and the potential for language development in the vernacular language. Sociolinguistic situation refers to how elements such as region, class, or other languages affect the use of Runga. Language development refers to activities such as creating an orthography, reading materials, and incorporating the language into education or other activities to promote its use. This paper affirms the importance of vernacular language development as well as showing that Runga is still a vital language used by many of the members of the community. Based on a survey conducted by the author during her master’s research, the expressed desires and opinions of the Runga community are considered and used to come to conclusions about the viability of language development, specifically that orthography development is desired by the community, as well as incorporating Runga into the educational system. The state of literacy and education in the Runga community is considered, as well as examples of other language development projects among other vernacular languages in Chad that have met with success, such as among the Daza people.